Pembuatan Karbon Aktif Dan Biopelet Dari Bambu Lokal Malang - Nircela Pradipta, Naresvara; Gatut Prakosa, Galit; Masykurrahmat, Faisal Hardin; Basuseno, Galang Dwi (Jurnal Penelitian Hasil Hutan, 2023)
Bamboo endemic species in Malang that have great potential for biomass utilization are apus, java, rampal, ori, and ampel bamboos. The fast-grown bamboo plant opens another potential to be used as an energy source as mixed pellets and carbon sources. In this study, the biopellet was made from bamboo powder that sieved with 40 and 60 mesh as initial treatment, then formed with pellet mold and dried. The products were tested according to SNI-8675-2018: Pellet. Furthermore, the carbon was made from mashed charcoal, where the powder than was activated using HCl solution with different concentrations namely 10% and 15%. The quality was tested according to Technical Activated Charcoal Standard (SNI 06-3730-1995). The results were tested by ANOVA to see the interaction of bamboo species and the pretreatment used. Rampal and Ori biopellets met the the SNI and has the highest calorific value. While the Ampel, Apus, Ori and Rampal bamboo carbon have the highest iodine absorption of 785,39 mg/g.